2021
DOI: 10.18231/j.ijcap.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Different approaches for teaching and learning anatomy and future directions

Abstract: Anatomy has been educated using different methods including didactic lectures, practical sessions based on models, cadaveric dissection, and computer-based learning. Covid-19 pandemic crisis led to an immediate alteration to distance learning by most of higher education institutions. The aim of this paper is to review the different traditional and recent anatomy educational approaches to know the appropriate approaches to use with Covid-19 pandemic and to plan for future education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…A systematic review conducted by Kazeminia et al in 2022 highlighted the positive impact of the FC method on teaching anatomy; the review revealed numerous advantages associated with this approach, including increased satisfaction, academic achievement, self-confidence, and overall outcomes in anatomy curricular [ 27 ]. A study conducted in China demonstrated an increase in the adoption of active learning methods, such as FCs, individualized tutoring, and small group discussions, during the COVID-19 pandemic [ 28 ]. Interactions in these active learning sessions primarily took place through real-time voice, text, or teaching management platforms like Rain Classroom, Xuexitong, or Blackboard.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review conducted by Kazeminia et al in 2022 highlighted the positive impact of the FC method on teaching anatomy; the review revealed numerous advantages associated with this approach, including increased satisfaction, academic achievement, self-confidence, and overall outcomes in anatomy curricular [ 27 ]. A study conducted in China demonstrated an increase in the adoption of active learning methods, such as FCs, individualized tutoring, and small group discussions, during the COVID-19 pandemic [ 28 ]. Interactions in these active learning sessions primarily took place through real-time voice, text, or teaching management platforms like Rain Classroom, Xuexitong, or Blackboard.…”
Section: Discussionmentioning
confidence: 99%
“…25 Indeed, a multimodal approach to teaching anatomy would be most effective and engaging for the learners; such approaches may include lectures, atlases, dissection/prosection, 3D printing, augmented or virtual reality, plastination, social media, videos, and online resources. 26,27 Unfortunately, medical schools in low-and middle-income countries may find the price excessive. Acquiring, preparing, and storing fresh cadaveric heads and brains can cost up to 100,000 PhP (1800 USD) whereas plastinated brain specimen can cost up to 400,000 PhP (7200 USD) each.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual dissection or digital dissection facilitates students with the innovative learning opportunities in veterinary anatomy. Nowadays, virtual dissection can be done with the help of animated anatomical structures on anatomy visualization table or virtual dissection table (Youssef, 2021). It is possible through the powerful software interactions where students can operate the computerised dissection on screen to accomplish through touch to understand the complex anatomic relationships (Darras et al., 2019).…”
Section: Traditional Methods Versus Virtual Learning Methods During C...mentioning
confidence: 99%